Experimental study on in-plane compressive response of irregular honeycombs. (April 2018) - Chen, Youming; Das, Raj; Battley, Mark
Compared with regular honeycombs, irregular honeycombs are more representative of real foams, and thus more suitable for the study of foam mechanics. In this paper, the deformation and failure progression in the irregular honeycombs are investigated by analysing the images captured in order to gain an improved understanding on foam failure. Irregular honeycombs with varying cell wall thickness, cell size and cell shape were manufactured using a three-dimensional printer and tested under compression. The behaviour of irregular honeycombs is found to be different from that of regular honeycombs. In irregular honeycombs, cell walls start to fracture at some point, initially at a low speed from multiple locations. The global stress reaches its maximum value shortly after the first fracture of cell walls. Only a few cell walls buckle in the specimens with cells of irregular shape. Fracture is more likely to occur to thin and long cell walls aligned within a medium angle (around 30 to 60°) to the compressive load. However, the susceptibility of a cell wall is to fracture is also affected by its neighbouring cell walls. Strong and stiff neighbouring cell walls could shield load away and protect it from breaking. Because of this, it is better to think of a weak spot as a region, rather than an individual cell or cell wall. Overall, the more uniform cell wall size and thickness are, the better the mechanical performance of cellular solids is.